Graced to go : step into the bigger bolder life that belongs to you - Osteen, Victoria (FaithWords, 2025)
"You were not meant to live stuck. Maybe you've had glimpses of something much bigger, better, and higher for your life. Maybe, when you've let yourself dream God-dreams, you've seen things that seemed completely impossible. They're not impossible-not once you understand that Jesus has given you "grace to go" for every situation and to overcome every challenge. In Graced to Go, Victoria Osteen encourages you to leave your fear behind and take the first step in the direction that God is calling you. Even the smallest step can get you moving towards your better future. Drawing from the lives of beloved Bible characters who felt stuck in difficult circumstances or faced seemingly-insurmountable odds-including Gideon, Abraham, Esther, and Moses-Victoria helps you see that when they trusted Him and took a step, God blessed them with grace to go. She walks readers through seven ways God prepares us for our own battles. When God calls us, we are graced: -In the strength you have -In the position you're in -With eyes to see the good -Knowing you matter -Releasing your blessing -With no regrets -Trusting God When God calls us, we are graced with the strength, courage, and gifting we need to face whatever challenge is before us. This encouraging, empowering, and inspiring book will help you to move toward all the favor and blessing God has for you"-- Provided by publisher.